How the brain learns mathematics - Sousa, David A. 4 0 16; 5 (Thousand Oaks, California : Corwin Press, 2008)
Explains how to apply cognitive mechanisms to improve student's understanding of mathematics, and includes various ways to differentiate instruction for preschool through secondary school students, and examines number sense, lesson plans, memory systems, ways to detect difficulties, and provides connections to the national standards.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Study and teaching.;Physiological aspects.;Physiological aspects. -- Mathematics;Learning, Psychology of.;Learning;Psychology of learning.;Learning; 20; 2